Some Aspects of Management of Enterprises Production Activity (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article is devoted to theoretical aspects of management of enterprises production activity. The characteristic definitions of «management» and «governance» and based on them formulated their own understanding of the term «management of production activity». The main approaches of the management of enterprises production activity are distinguished.It is proved that the effective management of production activities of the enterprise, its principles and functions provides a «survival of the enterprise». The principles, methods and functions of management of enterprises production activity are presented and discovered at the article.On the basis of the conducted researches, that development of integral control system by production activity foresees the account of principles, methods and functions of management of enterprise production activity.
Keywords: management, governance, production activity, functions of management, principles management